2007
DOI: 10.1038/sj.gene.6364368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the genetic restriction of virus-specific T-cell responses in hepatitis C virus infection

Abstract: The immunobiology of hepatitis C virus (HCV) is significantly influenced by the host immune response to the virus, especially by virus-specific T-cell responses. Virus-specific T cells are restricted by human leucocyte antigen class I and II molecules. Of note, associations between these polymorphic loci and outcome and course of HCV infection have been reported in large and well-documented cohorts. This review will briefly summarize these studies and focus especially on the immunological and virological basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 117 publications
(135 reference statements)
1
13
0
Order By: Relevance
“…We additionally examined the references cited in each paper, including several review papers. (6;7;19;20)…”
Section: Methodsmentioning
confidence: 99%
“…We additionally examined the references cited in each paper, including several review papers. (6;7;19;20)…”
Section: Methodsmentioning
confidence: 99%
“…HLA class I molecules are recognized by NK cells through killer immunoglobulin-like receptors (KIR) [17,18]. Recent studies have indicated that an HLA-class I/KIR complex is associated with the pathogenesis and susceptibility of type-1 diabetes mellitus [19,20,21], psoriatic arthritis [22], ankylosing spondylitis [23], hepatitis B [24], and hepatitis C [25]. In particular, the HLA-C/KIR complex has been investigated in context of many autoimmune diseases, infections and connective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It has, therefore, been suggested that different HLA class I alleles are associated with differential outcomes of HCV infection, e.g. viral clearance versus persistence [109] . Analysis of the role of HLA alleles in viral infections are hindered by multiple factors, including the wide polymorphism of HLA alleles, their association with other genetic characteristics e.g.…”
Section: Role Of the Host Hla Classⅰmentioning
confidence: 99%